2021
DOI: 10.1002/mame.202000818
|View full text |Cite
|
Sign up to set email alerts
|

Polyethyleneimine‐Mediated Polyamide Composite Membrane with High Perm‐Selectivity for Forward Osmosis

Abstract: Thin‐film composite (TFC) membranes comprised of a polyamide (PA) selective layer upon a porous substrate dominate the forward osmosis (FO) membrane market. However, further improvement of perm‐selectivity still remains a great challenge. Herein, a polyethyleneimine (PEI) interlayer is intentionally designed prior to interfacial polymerization (IP) to tailor the PA layer, which thus improves the separation performance. The PEI interlayer not only improves the substrate hydrophilicity for adsorbing more diamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…This approach enabled the substrate to adsorb more amine monomers from aqueous solution and control the IP reaction with the release rate. 53 …”
Section: Different Methods For Preparing Tfni Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach enabled the substrate to adsorb more amine monomers from aqueous solution and control the IP reaction with the release rate. 53 …”
Section: Different Methods For Preparing Tfni Membranesmentioning
confidence: 99%
“…51 PEI deposition of a carboxylated polyacrylonitrile (PAN) substrate was used to control the subsequent IP reaction by modulating the diffusion rate of the -NH 2 monomer with PEI. 53,54 In addition, the hydrophilic interlayer formed by PEI and PDA codeposition also controls the subsequent IP reaction. 47,48,55,56 Dopamine self-polymerizes into PDA under weakly alkaline conditions at pH = 8, and the surface of the substrate forms a stable surface coating.…”
Section: Selection Of Interlayer Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the TFC membrane of a commercial PAN substrate exhibited a favorable water permeability flux of 16.1, LMH, and an extremely low reverse salt flux (1.25 gMH). Within this, polyethyleneimine (PEI) was utilized as an interlayer prior to the IP reaction to tailor the PA layer, which thus improved TFC-PAN membrane perm-selectivity performance due to the formed denser, thinner, and smoother PA layer [154]. The same modification technique was followed by Farman et al [155], in which the modified membrane showed a reasonable performance for concentrating the orange juice via the FO process.…”
Section: Commercial Pan-based Membranes In Fo Testmentioning
confidence: 99%
“…In addition, the hydrophilic modification of the substrate surface by coating method can also enhance the permeability of the substrate without changing its pore structure in the matrix. At present, researchers have successfully coated polyethyleneimine (PEI) on PAN, 24 polydopamine (PDA) on PVC, 25 carbon nanotubes (CNTs) on PES, 12 and PDA nanoparticles on PAN nanofibers 26 in order to enhance the hydrophilicity and permeability of the substrate.…”
Section: Introductionmentioning
confidence: 99%